Challenging Topics in Neuroanesthesia and Neurocritical Care - Khan, Zahid Hussain; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book focuses on controversial issues in neuroanesthesia and neurocritical care that in general have been subjected to insufficient professional scrutiny. The book is in three parts, the first of which is devoted to topics relating to traumatic brain and spinal cord injury, such as brain tissue oxygenation, the role of biomarkers, and diagnosis of brain death. Aspects of airway and pain management are then addressed, covering, for example, airway management in an emergency setting, airway evaluation in the edentulous patient, and pain management in neurosurgery and after craniotomy. The final part of the book considers a wide range of other challenging subjects in the field of neuroanesthesia and neurocritical care. Throughout, much information is provided on the latest, state of the art management. The authors are acknowledged experts in the issues they discuss, and the book will be of interest for graduate and undergraduate students, residents, neuroanesthetists, neurointensivists, emergency medicine residents and specialists, fellows in neurocritical care and all those directly involved in the perioperative care of patients with head and neck pathology.
Part 1 Traumatic And Spinal Cord Injury -- Intracranial Compliance, Traumatic Brain Injury and Management -- Advanced Monitoring in Neurocritical Care: Brain tissue Oxygen Pressure -- Predictors of Outcome in Traumatic Brain Injury -- Understanding the Process of Brain Death Declaration Through Real-Life Scenarios -- Paroxysmal sympathetic Hyperactivity Following Acute Acquired Brain Injury -- Spinal Cord Injury -- Aneurysmal Subarachnoid Hemorrhage -- Part 2 Airway And Pain Management -- Airway Management in Neurosurgical Procedures (Along with Ventilation Management) -- A New Airway Assessment for Edentulous Patients and Its Potential Role in Neurocritical Care -- Airway Management in Neurocritical Care -- Postoperative Pain Management After Craniotomy -- Part 3 Neuroanesthesia And Neurocritical Care -- Anesthesia For Awake Craniotomy -- TIVA In Neurosurgery -- Anesthetic Challenges In Pediatric Cranio-Facial Surgeries -- Acromegaly: Do They Pose airway Problems? -- Airway and Fluid Management of Patients in a Prone Position -- Anesthesia Considerations For Posterior Fossa Surgery -- Anesthesia For Pituitary Surgery -- Venous Air Embolism in Neurosurgical Patients -- Blood Glucose Concentration in Neuro-Patients -- Anesthesia for Deep Brain Stimulation -- Intra-operative Magnetic Resonance Imaging (iMRI) -- Sedation In Neurocritical Care Units (NICU) -- Transcranial Doppler and Transcranial Color-Coded Duplex Sonography -- The Conundrum of Postoperative Hematoma in Intracranial surgery -- Neuroprotection in Neuroanesthesia And Neurocritical Care -- Sepsis And Septic Shock.
Keywords: Medicine; Anesthesiology; Emergency medicine; Neurosurgery; Medicine & Public Health; Anesthesiology; Emergency medicine; Neurosurgery